Pedogenesis and geochemistry of saltmarsh soils from the Brazilian coast - Romero, Danilo Jefferson (2020)
Saltmarshes are transitional ecosystems between dry land and coastal environments and have characteristics of both environments. Also, their biota is adapted for periods of anaerobiosis with water saturation and changes in salinity. Furthermore are responsible for several ecosystem services directly or indirectly associated with soils. Despite the increase in research on the subject, the saltmarshes soils are still poorly studied in the world, and there are no studies in Brazil that describe the morphology and classification of these soils. For that, it is necessary (1) to analyze the studies of saltmarshes in the world and their relations with the soil; (2) to evaluate the morphological, chemical and physical characteristics of these soils in Brazil; (3) Relate the geochemistry of iron to the pedogenetic processes in these soils; (4) Discuss the relationship between iron dynamics in a transition between mangroves and saltmarshes in a tropical climate. For this, two contrasting regions of salt marshes in Brazil (tropical and subtropical climate) were analyzed. Chemical analyzes (cations, pH, Eh, C.E.), particle size and sequential iron analyzes were performed in both areas. Thus, saltmarsh publications are more related to the use of the terminology of \"sediment\" than \"soil\", with 794 (65%) and 437 (35%) publications respectively. However, Bragança saltmarsh soil was classified as Gleissolo Tiomórfico órtico sódico, and Laguna soils were Gleissolo Tiomórfico órtico sódico and Gleissolo Tiomórfico órtico típico. Their differences were related to the higher iron content on Pará than Santa Catarina, and to the iron forms, wherein Para it is more oxide forms (low and high crystallinity), and in Santa Catarina is in sulphate form. The iron-related processes of sulfuricization and sulfidization were observed in Pará and Santa Catarina respectively. In Bragança the saltmarsh soils differ from mangroves due to the elevation of saltmarsh, which reduced the inundation and has favoured to pyrite oxidation (sulfuricization process), while in mangrove soil portion of iron is retained as pyrite, once organic matter and sulphates are available.